Effect of the application of green manures on the growth and performance of Phaseolus vulgaris - Jamioy, Diego David (2018)
The cultivation of Phaseolus vulgaris is of vital importance for the Latin American peasant economy, since it is one of the basic ingredients of the diet. In Colombia around 104 175 hectares are cultivated with a production of 130 988 tons per year, an insufficient quantity to supply domestic demand, so it is necessary to increase the yield of this crop without increasing production costs. Therefore, in this investigation the performance of Phaseolus vulgaris was estimated with the application of Arachis pintoi as a green manure in relation to growth and yield, for which 6 treatments with a control were established in the house of meshes, a design was used of complete blocks at random with 4 blocks. The treatments consisted in the application of fresh green manure incorporated into the soil (T1) and on the surface (T2), dry green manure incorporated into the soil (T3) and on the surface (T4) and green manure ash incorporated into the soil (T5) and on the surface (T6), the green manure was not applied to the control. At the end of the experiment, variables associated with the accumulation of dry matter and variables associated with yield were evaluated. The results obtained showed statistical differences (p≤0.05) between treatments for most of the variables evaluated. The best performances in growth and yield were presented from highest to lowest in T2, T4 and T1, and the lowest performing in descending order were T6, control and T5. According to the results obtained, it is concluded that the application of green manure contributes to increase the dry biomass and the yield of Phaseolus vulgaris, but this increase is not related to the nutrients provided by the green manure, as the treatments with only ashes were those who presented the lowest performances in the variables evaluated.